Desain Tata Ruang Filing Poliklinik JKN Berdasarkan Lingkungan Fisik yang Ergonomis - Mochammad Arief Darmawan; Mochammad Choirur Roziqin; Feby Erawantini (Politeknik Negeri Jember, 2020)
The physical environment is all that exists around the workplace that can affect employees both directly andindirectly. Several problems exist in the JKN Polyclinic filing room at Pertamina Central Hospital, amongothers, the room is not large, some documents RM are not stored in the available shelves, there is one light sothe filing room is not bright enough. The purpose of this study is to design a JKN polyclinic filing layout basedon an ergonomic physical environment at Pertamina Central Hospital. This research is qualitative, with datacollection techniques carried out by observation, interviews, and documentation. The results of this study areto produce a new JKN Polyclinic spatial filing design at Pertamina Jakarta Central Hospital following anergonomic physical environment. Spacious room for new filing room measuring 35 mÂ² with the addition ofsupporting facilities such as 57 medical record shelves for the needs of the next 5 years, 1 piece of AC (AirConditioning) measuring 1PK, 3 lamps measuring 20 watts, and additional ventilation of 5.25 mÂ². It isrecommended to Pertamina Central Hospital to add facilities such as medical record shelves, repairs ofrefrigeration equipment such as AC (Air Conditioning), lights, and indoor air ventilation. These facilities arevery important because they affect the comfort and health of officers working in the filing room.